A CoNi telluride heterostructure supported on Ni foam as an efficient electrocatalyst for the oxygen evolution reaction. Issue 20 (1st September 2022) - Qi, Yu; Yang, Zhi; Dong, Youcong; Bao, Xiao-Qing; Bai, Jilin; Li, Hong; Wang, Mitang; Xiong, Dehua
Abstract : The excellent oxygen evolution reaction performance of a CoNi telluride heterostructure (0.4CoNi LDH@Te-180C) can be attributed to the inherent layered structure, interconnected nanoarray structures and the synergistic effect of Co and Ni species. Abstract : Herein, a CoNi telluride heterostructure nanosheets consisting of cobalt nickel layered double hydroxide (CoNi LDH) and nickel telluride were prepared on the surface of Ni foam by a simple one-step hydrothermal method. The CoNi telluride heterostructure (CoNi LDH@Te) not only provides a high specific surface area with abundant active sites from CoNi LDH, but also shows a high conductivity of nickel telluride. The optimized 0.4CoNi LDH@Te-180C electrode exhibits an impressive oxygen evolution reaction activity, which needs an overpotential of 360 mV to attain an anodic current density of 10 mA cm −2, with a Tafel slope of 56.6 mV dec −1, much smaller than those of Ni-Te-180C ( η 10 = 423 mV; a Tafel slope of 65.1 mV dec −1 ) and those of bare NF ( η 10 = 445 mV; a Tafel slope of 97.6 mV dec −1 ). Moreover, 0.4CoNi LDH@Te-180C also shows excellent long-term stability, which can maintain continuous electrolysis for 18 hours with only a little degradation of 23 mV. The excellent oxygen evolution reaction performance of CoNi telluride can be attributed to the inherent layered structure, interconnected nanoarray structures and the synergistic effect of Co and Ni species.